Source and geological significance of Jurassic asphalt in the Ruoqiang Sag of Southeast Depression, Tarim Basin, Northwestern China - Lan, Xiaodong; Bai, Zhongkai; Yang, Youxing; Jiang, Zhenglong; Zhang, Jile (Frontiers in Earth Science, 2024)
The Southeast Depression of the Tarim Basin has a very low petroleum exploration degree, and currently, no industrial oil and gas have been discovered. Many hydrocarbon shows exist in the Ruoqiang Sag, where hydrocarbon sources and accumulation processes are unclear. Only two potential Jurassic hydrocarbon source rocks developed in the Ruoqiang Sag, the Yangye (J2y) lacustrine mudstone of the Middle Jurassic and the Kangsu (J1k) coal-bearing mudstone of the Lower Jurassic. In this study, the Jurassic asphalt found in the QD1 well, combined with the source rocks of drilling cores and outcrops, was used to explore the possible hydrocarbon source and forming process in the Ruoqiang Sag using oil-source correlation and hydrocarbon accumulation geochronology methods. The asphalts have lower light and heavy rare earth fractionation than the J2y mudstone, and the total rare earth element (ΣREE) content, chondrite-normalized curves, and δEu and Y/Ho values are similar to those of the J1k mudstone, especially for the J1k coal. The n-alkane ratios of the carbon preference index and the odd-to-even preference (OEP) of Jurassic asphalts are greater than 1.0, indicating that its source rock has experienced low thermal evolution. All Jurassic samples have similar source-related biomarkers but different maturity-related parameters, and the thermal evolution degree of asphalt is close to the J1k mudstone and coal but slightly higher than the J2y mudstone. Meanwhile, rhenium–osmium isotopes show the asphalts are formed in 192+30/−45 Ma, which is similar to the J1k sedimentation time. The asphalts contain coal macerals and probably derived from the asphaltene precipitated by the J1k coal during the early coalification. The low abundance of 25-norbornanes with a non- or slight petroleum biodegradation degree indicates the asphalt was generated relatively late and migrated into the J2y formation along the faults, possibly accompanied by the striking activities of the Altyn Tagh Fault during the Neotectonics movement. This study provides evidence for the J1k coal-bearing strata serving as the effective source rock in the Ruoqiang Sag and increases confidence for Jurassic petroleum exploration in the Southeast Depression of the Tarim Basin. The structural and lithological traps near hydrocarbon source stoves, where Jurassic strata were deeply buried and far from the Altyn Tagh Range, are favorable oil and gas exploration targets.